Economic analysis of the U.S. Department of Agriculture’s value-added producer grants program - Oswald, Dustin J. (Kansas State University, 2011)
The 2002 Farm Bill Rural Development Title created new programs to encourage the development of businesses designed to convert commodities to value-added products. This thesis identifies determinants of business development success for Value-Added Producer Grant (VAPG) recipients. Success is categorized in nine different stages of development:(1) creation of an idea, (2) formation of the idea into a written plan as a feasibility study, business plan, or marketing plan, (3) formation of an organizational structure for the idea, (4) the hiring of a manager or employees for the idea, (5) raise capital for the idea through equity drives, (7) creation of the idea into a product in a facility, (8) distribute and sell the product, (9) and whether the product was being sold in March of 2006. The data involves information on 621 grant recipients. Two econometric models are used to evaluate the data. The number of USDA Rural Business and Cooperative Employees, the value-added producer grant amount divided by the number of producers in the organization, the 2006 organizational sales divided by the number of producers in the respective organization, and the total production of the organization divided by the national production of the respective crop were significant variables. These four size variables had a negative impact on an organization being in steps one though eight, but a positive impact on being in step nine, which was the successful stage of business development. (such as dairy, flowers, fruit, nuts, specialty meats, wheat, and wine were positively associated with successful VAPG grant recipients. Illinois, Kansas, Minnesota, Missouri, and Wisconsin had significantly greater odds of success in business development also.
Keywords: Value-added agriculture; Agricultural economics; Rural development; Agriculture, General (0473); Economics, Agricultural (0503); Education, Agricultural (0517)